A method of increasing labour productivity in construction - A. A. Lapidus (Vestnik MGSU)
Introduction. The attempt to solve the problem of labour productivity determination is made, the method of increasing it is considered. The representation of labour productivity in the form of a complex system, formed on the basis of the provisions of system engineering in construction, makes it possible to create a decomposition of its components in the form of factors and parameters influencing them.Materials and methods. Labour productivity as a complex construction system with a large number of subsystems forming it is considered. A mathematical model of labour productivity, formed from factors and parameters influencing them, makes it possible to determine the actual value of labour productivity.Results. The actual value of labour productivity is proposed to be compared with the normal value — the value that ensures the required labour productivity in construction, its individual type or even the production structure. The subsystems under study are taken as the main factors, each of them is taken as factors affecting labour productivity. Others can be added to them, for example, unification of design solutions or some other factors. Each of the listed factors is characterized by the parameters creating it. As well as the factors, the parameters creating them represent an open subsystem, the content of which is the subject of research. The result is the construction of a mathematical model of labour productivity.Conclusions. The solution of the direct problem — determination of the actual value of labour productivity based on the value of factors and the parameters influencing them can be carried out for comparison with the normal value of labour productivity and determination of the actual growth of labour productivity. The solution to the inverse problem is to achieve the target labour duration by assigning to the factors and parameters influencing them the values necessary to solve the task.